2015
DOI: 10.5958/0974-0279.2015.00026.9
|View full text |Cite
|
Sign up to set email alerts
|

Examining Export Volatility, Structural Breaks in Price Volatility and Linkages between Domestic and Export Prices of Onion in India

Abstract: This paper has investigated the export volatility, identified the structural breaks and determined the shortrun and long-run relationships between onion export and domestic prices using cointegration and Granger causality test. The study is based on the monthly arrival data of five major regulated markets from three major onion-producing states of India, namely Azadpur from Delhi, Lasalgaon, Pune and Solapur from Maharashtra, Bangalore and Hubli from Karnataka along with the export price. After checking for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…However, on several occasions, especially post-2008 global food crisis, the domestic prices have been higher than export prices (Figure 9(a)). Paul et al (2015) also report similar evidence.…”
Section: Exports and Export Policiessupporting
confidence: 59%
“…However, on several occasions, especially post-2008 global food crisis, the domestic prices have been higher than export prices (Figure 9(a)). Paul et al (2015) also report similar evidence.…”
Section: Exports and Export Policiessupporting
confidence: 59%
“…Ajjan et al (2013) studies the market integration of the peas market in India and concluded that market has a price relationship and therefore an integrated one. Paul et al (2015) studies export volatility, structural price and the relationship betwee domestic prices and export of red onion in India, in which, co-integrated models and Granger causality tests are used. The results show that prices in all market shares are stable in the long-term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have used WT, co-integration tests, and Granger causality tests to identify the existence of long-term relationships [24]. Paul et al [25] examined export volatility, and identified short-and long-term relationships between onion export and domestic prices using co-integration analysis and Granger Causality. Volatility estimating is especially crucial for organizations that trade in stocks and manage portfolios [26].…”
Section: Introductionmentioning
confidence: 99%